2023
DOI: 10.3390/vaccines11040749
|View full text |Cite|
|
Sign up to set email alerts
|

Myocarditis and Pericarditis following COVID-19 Vaccination in Thailand

Abstract: Background: Myocarditis and pericarditis cases following Coronavirus 2019 (COVID-19) vaccination were reported worldwide. In Thailand, COVID-19 vaccines were approved for emergency use. Adverse event following immunization (AEFI) surveillance has been strengthened to ensure the safety of the vaccines. This study aimed to describe the characteristics of myocarditis and pericarditis, and identify the factors associated with myocarditis and pericarditis following COVID-19 vaccination in Thailand. Method: We carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Regardless of serious outcomes, most studies reported the opposite trend: females have a higher risk than males, and younger adults have a higher risk than older adults [ 3 , 4 , 5 , 6 , 7 , 8 ]. For SAE after the primary doses, some conditions dominated in younger individuals, such as myopericarditis [ 30 , 31 , 32 ] and anaphylaxis [ 4 , 28 ], which was similarly found in this study after booster doses. This study further evaluated the risk of all SAE, in which half of the cases were cardiovascular events (other than myopericarditis) and thrombotic events.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Regardless of serious outcomes, most studies reported the opposite trend: females have a higher risk than males, and younger adults have a higher risk than older adults [ 3 , 4 , 5 , 6 , 7 , 8 ]. For SAE after the primary doses, some conditions dominated in younger individuals, such as myopericarditis [ 30 , 31 , 32 ] and anaphylaxis [ 4 , 28 ], which was similarly found in this study after booster doses. This study further evaluated the risk of all SAE, in which half of the cases were cardiovascular events (other than myopericarditis) and thrombotic events.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, the risk of SAE following a booster dose in the younger males could be underestimated due to rare younger males receiving a booster dose. Compared to a countrywide study that used the same databases of primary doses, there was a larger study population of young males that made it possible to capture 137 cases of myocarditis and pericarditis and report the highest risk in young males [ 30 ]. The symptoms of myopericarditis in the young were mild, and they recovered without permanent heart damage [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports significantly impact public willingness to receive vaccinations, consequently affecting vaccination rates [ 7 , 19 , 20 ]. Of particular concern are the severe adverse events associated with booster vaccines, such as vaccine-induced myocarditis and pericarditis, multisystem inflammatory syndrome in children (MIS-C), and multisystem inflammatory syndrome in adults (MIS-A) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The question of whether the incidence and severity of side effects increase with additional doses is of utmost importance and urgently requires detailed clinical reports to understand the current situation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%